Race, nationality, and partisanship shape U.S. public support for climate disaster aid: Evidence from two survey experiments - Volha Charnysh; Jared S. Kalow; Evan S. Lieberman; Erin E. Walk (PLoS ONE, 2026)
We examine how race, nationality, and political partisanship influence U.S. public support for climate-related disaster aid. Using two preregistered survey experiments (N = 7,511), we varied the race (Black/White) and nationality (U.S./Brazil or South Africa) of flood victims depicted in an artist’s rendering of a fictional disaster. Respondents were significantly less supportive of aid to Global South victims than U.S. victims, with the gap largest among Republicans. Race effects were smaller and context-dependent: domestically, White Republicans expressed less generosity towards Black than White victims, while White Democrats showed the opposite tendency. Our analysis provides suggestive evidence that perceptions of social distance and deservingness shape willingness to provide climate aid across racial and national lines.